The Role of Cash Waqf-Linked Sukuk as a Sustainable Financing Instrument in Supporting National Economic Development - Nurjanna Ladjin (Pt. Anagata Sembagi Education, 2026)
Indonesia faces a persistent national development financing gap that conventional fiscal instruments and commercial debt alone cannot close, particularly for social-infrastructure and inclusive-growth agendas linked to the Sustainable Development Goals (SDGs). Cash Waqf-Linked Sukuk (CWLS) has emerged since 2020 as a hybrid Islamic social-commercial finance instrument that channels the principal-protected returns of cash waqf into sovereign sukuk, generating a perpetual yield stream for productive social programs. This article synthesizes twenty-five recent scholarly sources (2021–2026) to examine how CWLS functions as a sustainable financing mechanism supporting national economic development. Using a qualitative descriptive literature-review method, documents were screened, classified, and analyzed thematically across five domains: infrastructure, food security and agriculture, MSME and community empowerment, post-pandemic recovery, and cross-country comparison. The review finds that CWLS offers a principal-safe, Shariah-compliant channel that simultaneously mobilizes idle cash waqf and diversifies the government's sukuk investor base, but its impact remains constrained by low public literacy, limited Nazhir institutional capacity, and fragmented distribution channels. The novelty of this article lies in integrating dispersed sector-specific findings into a single SDG-mapped conceptual framework and identifying an emerging convergence between CWLS and green-sukuk financing. Policy implications for scaling CWLS as a sustainable national financing instrument are discussed